'Cobrançosa' Olive Oil and Drupe: Chemical Composition at Two Ripening Stages. (8th January 2014) - Sousa, Cláudia; Gouvinhas, Irene; Barreira, Diana; Carvalho, Maria Teresa; Vilela, Alice; Lopes, João; Martins‐Lopes, Paula; Barros, Ana I.
Abstract: The chemical composition and organoleptic characteristics of olive oils may be influenced by genotype and some agronomic factors like olive drupe harvesting date. The aim of this work was to study the influence of olive ripening stage on chemical parameters and the organoleptic profile of fruits and oils of one of the main olive Portuguese cultivars ( Cobrançosa ). Six different Cobrançosa clones, which were harvested at two different ripening stages in the same olive growing area, were analyzed to evaluate phenolic compounds, ortho ‐diphenols, flavonoids and antioxidant activity and were characterized in terms of sensorial parameters. These clones have also been classified according to the yield of production. The lowest values in phenolic content, ortho ‐diphenols, flavonoids and antioxidant activity occurred always in the same clone (110) in both ripening stages in olive fruits and olive oil. This clone has been previously identified as low yield. Also, the results revealed significant correlations between total phenolics and antioxidant activity ( R 2 = 0.932, P < 0.0001), between ortho ‐diphenols and antioxidant activity ( R 2 = 0.9445, P < 0.0001) and between flavonoids and antioxidant activity ( R 2 = 0.9263, P < 0.0001) on olive oil samples. The sensorial parameters that have been affected in olive oils were herbaceous aroma and flavor, and bitter taste that increased with the ripening process.